The Ontogeny of the Endocrine Pancreas in the Fetal/Newborn Baboon - Quinn, Amy R. (2012)
BACKGROUND: Erratic regulation of glucose metabolism including hyperglycemia is a common condition of premature infants and is associated with increased morbidity and mortality. OBJECTIVE: To examine histological and ultra-structural differences in the endocrine pancreas in fetal (throughout gestation) and neonatal baboons. METHODS: Twelve fetal baboons were delivered at 125 days (d) gestational age (GA), 140dGA, or 175dGA. Eight animals were delivered at term (185dGA); half were fed for 5d. Seventy-three non-diabetic adult baboons were used for comparison. Pancreatic tissue was studied utilizing light microscopy, confocal imaging and electron microscopy. RESULTS: The fetal and neonatal endocrine pancreas islet architecture became more organized as GA advanced. The percent areas of α-β-δ-cell type were similar within each fetal and newborn GA (NS), but were higher than the adults (P<0.05) regardless of GA. The ratio of β-cells within the islet (whole and core) increased with gestation (P<0.01). Neonatal baboons who survived for 5 days (feeding), had a 2.5-fold increase in pancreas weight compared to their counterparts euthanized at birth (P=0.01). Endocrine cells were found amongst exocrine ductal and acinar cells in 125,140 and 175dGA fetuses. Subpopulation of cells that co-expressed trypsin and glucagon/insulin show the presence of cells with mixed endo-exocrine lineage in fetuses. CONCLUSIONS: The fetal endocrine pancreas has no prevalence of a of α-β-δ-cell type with larger endocrine cell percent areas than adults. Cells with mixed endocrine/exocrine phenotype occur during fetal development. Developmental differences may play a role in glucose homeostasis during the neonatal period and may have long term implications.